Hands-on Fourier analysis by means of far-field diffraction. (17th August 2016) - Ceffa, Nicolo' Giovanni; Collini, Maddalena; D'Alfonso, Laura; Chirico, Giuseppe
Abstract: Coherent sources of light are easily available to university undergraduate laboratory courses and the demonstration of electro-magnetic wave diffraction is typically made with light. However, the construction of arbitrary patterns for the study of light diffraction is particularly demanding due to the small linear scale needed when using sub-micrometer wavelengths, limiting the possibility to thoroughly investigate diffraction experimentally. We describe and test a simple and affordable method to develop arbitrary light diffraction patterns with first year undergraduate or last year high school students. This method is exploited to investigate experimentally the connection between diffraction and the Fourier transform, leading to the development of the concept of spectral analysis of a (2D) signal. We therefore discuss the possibility of building a teaching unit for first year undergraduate or last year high school students on the interdisciplinary topic of spectral analysis starting from an experimental approach to light diffraction.